2019
DOI: 10.1016/j.humpath.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of claspin overexpression and its association with spheroid formation in gastric cancer

Abstract: Gastric cancer (GC) is one of the leading causes of cancer-related death worldwide. Spheroid colony formation is a useful method to identify cancer stem cells (CSCs). The aim of this study was to identify a novel prognostic marker or therapeutic target for GC using a method to identify CSCs. We analyzed the microarray data in spheroid body-forming and parental cells and focused on the CLSPN gene because it is overexpressed in the spheroid body-forming cells in both the GC cell lines MKN-45 and MKN-74. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In addition, CLSPN coexpresses with PDL-1, CD44, EGFR, p53 and acts as a poor prognosis fact in renal cell carcinoma (Kobayashi et al, 2020). Besides, some researches showed that overexpressed CLSPN leads to solid tumors poor prognosis and progression (Allera-Moreau et al, 2012;Wang et al, 2017;Kobayashi et al, 2019). However, its role in PCa is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CLSPN coexpresses with PDL-1, CD44, EGFR, p53 and acts as a poor prognosis fact in renal cell carcinoma (Kobayashi et al, 2020). Besides, some researches showed that overexpressed CLSPN leads to solid tumors poor prognosis and progression (Allera-Moreau et al, 2012;Wang et al, 2017;Kobayashi et al, 2019). However, its role in PCa is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that overexpression of claspin contributes to tumor proliferation in several human solid tumors, such as colon, lung, bladder, breast, ovarian, and cervical cancers . Previously, we identified upregulation of the CLSPN gene in spheroid body‐forming GC cell lines . We also reported that overexpression of claspin is found in 47% of GC cases and is associated with tumor progression in GC .…”
Section: Introductionmentioning
confidence: 71%
“…20 We also reported that overexpression of claspin is found in 47% of GC cases and is associated with tumor progression in GC. 20 Therefore, depending on the circumstances, claspin plays an ambivalent function of tumor suppression and promotion. To our knowledge, however, detailed function and expression profiles of the CLSPN gene in RCC have not previously been analyzed.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Oue et al showed that KIFC1 and KIF11, two members of the kinesin-14 family, were overexpressed in spheroids compared to parental cells [ 74 , 75 ], while their knockdown inhibited spheroid formation [ 74 , 76 ]. In a similar context, this group also reported the under-expression of the claspin (CLSPN) gene, which codes for a nuclear protein involved in DNA replication and S-phase regulation, in spheroids [ 77 ]. Recently, Lee et al demonstrated, using a limiting dilution protocol in a microwell-based culture chip, that gene expression of spheroid-forming cells was closely related to histological diffuse and intestinal type [ 78 ].…”
Section: Three D Multicellular Tumor Spheroid Modelmentioning
confidence: 99%